720 Dynamic Hip Screw vs Short Intra Medullary Nail - Which Is Safer for the Surgeon: A Retrospective Comparison of Radiation Exposure. (19th August 2022) - Noton, T; Khanom, S; Kazzazi, F; Magill, H; Bagouri, E; Abd Wahab, EH; Vasireddy, A
Abstract: Aim: Dynamic hip screws (DHS) and short intra medullary (IM) nails are fixation methods used for neck of femur (NOF) fractures. Both require fluoroscopic assistance within the operating theatre, therefore exposing the surgeon and patient to ionising radiation. There is minimal literature investigating radiation exposure. Aims of this study are to compare the radiation doses in each procedure and to estimate a normalised dose. Method: Retrospective data analysis was carried out for patients who underwent fluoroscopically assisted surgical management of NOF fractures using DHS and short IM nail over a 3-year-period. Data was sourced using electronic operative records and Sectra PACS imaging software. Radiation dose parameters collected were the cumulative dose in milligrays (mGy), cumulative dose area product (DAP) (Gy.cm2) and time of exposure in minutes and seconds. Statistical analysis was performed using SPSS statistical software. Results: A total of 56 patients were treated with a DHS, and 46 with short IM nails (Short TFNA - Synthes). 79% of DHS cases were for extra capsular neck of femur fractures versus 100% of short IM nails. Cumulative radiation dose for the DHS group demonstrated a mean of 6.007mGy, compared to 1.153mGy for the short IM nail. Mean exposure times were 1:39 for the DHS group compared to 1:32 for the IM nail. Conclusions: Our study showed the difference in cumulative radiation exposure was significantly less when using the short IM nail compared to the DHS. Additional radiation should be considered a safety hazard for the surgeon, theatre staff and patients.